2011
DOI: 10.5054/tj.2011.259955
|View full text |Cite
|
Sign up to set email alerts
|

Discourse Prosody and Teachers' Stated Beliefs and Practices

Abstract: Over the past few decades, research has demonstrated the important role that prosody (i.e., stress, rhythm, intonation) plays in the intelligibility of speakers of English as a second language (ESL). Yet the impact of this research on teacher cognition—the beliefs and knowledge that teachers possess in relation to their classroom practices—has received limited attention. This article explores how research into English prosody has influenced pronunciation instruction in the ESL classroom, teachers' knowledge an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 28 publications
2
54
1
Order By: Relevance
“…It was also revealed that lack of educational resources and insufficient knowledge toward evaluating learners' pronunciation contributed to their reluctance to teach English pronunciation. In another study done by Baker (2011), it was shown that teachers who had a training in pronunciation preferred the instruction of supra-segmental aspects of English pronunciation. Unfortunately, a lot of these teachers did not have enough confidence in the instruction of some features of pronunciation.…”
Section: Review Of Literature On Teachers' Negligence In Teaching Engmentioning
confidence: 99%
See 3 more Smart Citations
“…It was also revealed that lack of educational resources and insufficient knowledge toward evaluating learners' pronunciation contributed to their reluctance to teach English pronunciation. In another study done by Baker (2011), it was shown that teachers who had a training in pronunciation preferred the instruction of supra-segmental aspects of English pronunciation. Unfortunately, a lot of these teachers did not have enough confidence in the instruction of some features of pronunciation.…”
Section: Review Of Literature On Teachers' Negligence In Teaching Engmentioning
confidence: 99%
“…6, No. 6;2016 for weak and strong forms of the words and this causes unusual sounds in their pronunciation. Teachers are advised to use appropriate exercises for the weak and strong words for their learners (Bekleyen, 2011).…”
Section: Review Of Literature On Teachers' Negligence In Teaching Engmentioning
confidence: 99%
See 2 more Smart Citations
“…Several methodological perspectives are available for the explicit teaching of pronunciation (Derwing and Munro 2005;Foote, Holtby, and Derwing 2011) but instructors often do not feel comfortable explicitly teaching pronunciation (Burns 2006;Baker 2011;Foote, Holtby, and Derwing 2011;reported in Koike 2014), either because they find it difficult to listen analytically to the students' pronunciation, identify errors, and suggest remedies, or because they give priority to other aspects of communicative competence such as the acquisition of vocabulary and morphosyntax. Prosody awareness training is the most marginalized activity in the training of interpreters though prosody plays a key role in communicating the message.…”
Section: Introductionmentioning
confidence: 99%